PPARβ mediates mangiferin-induced neuronal differentiation of neural stem cells through DNA demethylation. (May 2022) - Ye, Xiujuan; Wu, Yuanfei; Xu, Jiamin; Liu, Hui; Wang, Huan; Li, Qingfeng; Li, Qingqing; Xuan, Aiguo
Abstract: Adult hippocampal neurogenesis (AHN) is heavily implicated in the pathogenesis of various neuropsychiatric disorders. The mangiferin (MGF), a bioactive compound of the mango, reportedly produces biological effects on a variety of neuropsychiatric disorders. However, the function and underlying mechanisms of MGF in regulating hippocampal neurogenesis remain unknown. Here we discovered that the transcriptome and methylome of MGF-induced neural stem cells (NSCs) are distinct from the control. RNA-seq analysis revealed that the diferentially expressed genes (DEGs) were signifcantly enriched in the PPARs. Furthermore, we found that MGF enhanced neuronal differentiation and proliferation of neural stem cells (NSCs) via PPARβ but not PPARα and PPARγ. The combination of WGBS and RNA-seq analysis showed that the expression of some neurogenesis genes was negatively correlated with the DNA methylation level generally. We further found that PPARβ increased demethylation of Mash1 promoter by modulating the expressions of active and passive DNA demethylation enzymes in MGF-treated NSCs. Importantly, genetic deficiency of PPARβ decreased hippocampal neurogenesis in the adult mice, whereas the defective neurogenesis was notably rescued by Mash1 overexpression. Our findings uncover a model that PPARβ-mediated DNA demethylation of Mash1 contributes to MGF-induced neuronal genesis, and advance the concept that targeting PPARβ-TET1/DNMT3a-Mash1 axis regulation of neurogenesis might serve as a novel neurotherapeutic strategy. Graphical Abstract: ga1